LAND SURFACE TEMPERATURE RESPONSES TO VEGETATION AND SOIL MOISTURE INDEX USING LANDSAT-8 DATA IN LUONG SON DISTRICT, HOA BINH PROVINCE - Dai Nguyen, Vo; Hai Hoa, Nguyen; Quyet, Nguyen; Duy Quang, Pham (Journal of Forestry Science and Technology, 2021)
Land surface temperature (LST) is considered as a key factor in natural processes. Remote sensing data, including Landsat-8 data, offers numerous opportunities to better understand the land processes. This study has conducted to construct land use and land cover map in 2020 using NDVI thresholds. The study then calculated the LST, NSMI, NDBI and Slope of Luong Son district, Hoa Binh province using Landsat-8 OLI/TIRS data. Models showing the relationships between the LST and independent variables (NDVI, NSMI, NDBI and Slope) were developed using R statistical software. As a result, NDVI used for land use and land cover mapping is confirmed with the overall accuracy assessments of 92.0% and Kappa coefficient of 0.85. Study developed 37 linear regression models, one of them was selected and used to predict the LST in Luong Son district. The selected model (R2 > 0.60, Pvalue < 0.0001) confirms that an increase of built-up land (NDBI) and loss of vegetation cover (NDVI) become a serious threat to the increase in land surface temperature in Luong Son district. This study implies that an increase of vegetation cover would lead to a slight decrease in land surface temperature, and built-up land expansion would be one of main responsible drivers for an increase of the LST. The only way to mitigate this risk is to increase additional vegetation cover in the built-up land; to both protect the existing forests and promote afforestation activities, which can considerably reduce the land surface temperature.